Hyperthermia and targeting heat shock proteins: innovative approaches for neurodegenerative disorders and Long COVID - Smadja, David M.; Abreu, M. Marc (Frontiers in Neuroscience, 2025)
Neurodegenerative diseases (NDs) and Long COVID represent critical and growing global health challenges, characterized by complex pathophysiological mechanisms including neuronal deterioration, protein misfolding, and persistent neuroinflammation. The emergence of innovative therapeutic approaches, such as whole-body hyperthermia (WBH), offers promising potential to modulate underlying pathophysiological mechanisms in NDs and related conditions like Long COVID. WBH, particularly in fever-range, enhances mitochondrial function, induces heat shock proteins (HSPs), and modulates neuroinflammation—benefits that pharmacological treatments often struggle to replicate. HSPs such as HSP70 and HSP90 play pivotal roles in protein folding, aggregation prevention, and cellular protection, directly targeting pathological processes seen in NDs like Alzheimer's, Parkinson's, and Huntington's disease. Preliminary findings also suggest WBH's potential to alleviate neurological symptoms in Long COVID, where persistent neuroinflammation and serotonin dysregulation are prominent. Despite the absence of robust clinical trials, the therapeutic implications of WBH extend to immune modulation and the restoration of disrupted physiological pathways. However, the dual nature of hyperthermia's effects—balancing pro-inflammatory and anti-inflammatory responses—emphasizes the need for dose-controlled applications and stringent patient monitoring to minimize risks in vulnerable populations. While WBH shows potential interest, significant challenges remain. These include individual variability in response, limited accessibility to advanced hyperthermia technologies, and the need for standardized clinical protocols. Future research must focus on targeted clinical trials, biomarker identification, and personalized treatment strategies to optimize WBH's efficacy in NDs and Long COVID. The integration of WBH into therapeutic paradigms could mark a transformative step in addressing these complex conditions.